PERLAWANAN PANGERAN NATA DIRJA II TERHADAP KOLONIAL INGGRIS DI BENGKULU (1710-1719) - Caca Satria Vanbudi Vanbudi; Isjoni, M.Si Isjoni; Bedriati Ibrahim, M.Si Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
RESISTANCE PANGERAN NATA DIRJA II , IN ENGLISH COLONIALS IN BENGKULU (1710-1719) Caca Satria Vanbudi1, Prof. Dr. Isjoni, M.Si2, Dra. Bedriati Ibrahim, M.Si3Email:cacasatria81@gmail.com, isjoni@yahoo.com, Bedriati.ib@gmail.comCP : 085361771510 History Education Studies ProgramEducation Department of Social SciencesFaculty of Teacher Training and Education University of Riau Abstract: Prince Nata Dirja II was the son of the late Prince Nata Dirja I who was killed by British colonialism. Prince Nata Dirja II's hatred of British colonialism was also motivated by the British attitude which forced the Bengkulu people and made their slaves. Because of a great sense of hatred towards British colonial Prince Nata Dirja II and the people of Bengkulu united their determination and feeling to fight the British colonials and drove him out of Bengkulu. The purpose of this study was to determine the background of the resistance of Prince Nata Dirja II to British colonialism, to find out Prince Nata Dirja's resistance to British colonialism, and to find out the end of Prince Nata Dirja II's resistance to British colonialism. The method used in this study is the historical method. The research location is in the city of Bengkulu. When research starts from proposal seminars to Thesis examinations. Data collection techniques used are documentation techniques, library techniques, observation techniques. From the results of the study it can be concluded that this Prince Nata Dirja II played an important role in the resistance against the British colonial and Prince Nata Dirja II also succeeded in expelling the British colonial from Bengkulu. Key Words: Resistance, Prince Nata Dirja II, British Colonial.